Expectancy effects in tennis: The impact of opponents' pre-match non-verbal behaviour on male tennis players - Buscombe, R.; Greenlees, I.; Holder, T.; Thelwell, R.; Rimmer, M. (Journal of Sports Sciences, 2006)
In this study, we examined the impact of a male opponent's pre-match body language and clothing (general vs. sports-specific) on how his performances were judged by an observer. Forty male tennis players viewed videos of a male target tennis player warming up and then observed playing footage of the target. Each participant viewed the target player warming up displaying one of four combinations of body language and clothing (positive body language/tennis-specific clothing; positive body language/general sportswear; negative body language/tennis-specific clothing; negative body language/general sportswear). Participants rated the performance of the tennis player and gave their perceptions of the likely outcome of a tennis match with the target player. Analyses of variance indicated that clothing and body language had an interactive effect on both outcome expectations and ratings of performance. The findings support the contention that the initial impressions athletes form of their opponents can influence the way in which they judge the performances of opponents and their perceived likelihood of success against the same opponents.